Theranostic Graphene Oxide for Prostate Cancer Detection and Treatment. (27th August 2014) - Chavva, Suhash Reddy; Pramanik, Avijit; Nellore, Bhanu Priya Viraka; Sinha, Sudarson Sekhar; Yust, Brian; Kanchanapally, Rajashekhar; Fan, Zhen; Crouch, Rebecca A; Singh, Anant Kumar; Neyland, Bethany; Robinson, Kimberly; Dai, Xuemei; et al.
<x xml:space="preserve">Abstract</x> Although prostate cancer has been known for thousands of years, it is a major public health issue for men even in the 21st century. As the understanding of cancer biology and the signaling pathways advances, it is now well understood that the detection of prostate cancer circulating tumor cells (CTCs) is an invaluable tool for monitoring the progression and finding possible therapies. Driven by this need, in this article, the development of magnetic‐nanoparticle‐attached theranostic graphene oxide (GO) is reported for targeted capture of prostate CTCs, accurate diagnosis, and combined therapeutic action of prostate cancer. Reported results show that anti‐epithelial cell adhesion molecule (EpCAM) antibody and A9‐aptamer‐attached flower‐shaped magnetic nanoparticle‐bound 2D graphene can be used for selective capture and label‐free multicolor luminescence imaging of LNCaP prostate cancer cell from infected blood. Experimental data demonstrate that indocyanine green (ICG)‐bound A9‐aptamer‐attached theranostic GO is capable of external near IR 785 nm light‐driven combined synergistic photothermal and photodynamic treatment of prostate cancer. Possible mechanisms for targeted capture, accurate analysis, and combined therapeutic actions have been discussed. Experimental results show that the theranostic GO can have enormous potential for real‐life applications, once optimized properly in clinical settings.